2019
DOI: 10.1055/s-0039-1693152
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Considerations in Acute Disseminated Encephalomyelitis and the Interface with MOG Antibody

Abstract: Acute disseminated encephalomyelitis (ADEM) is a common yet clinically heterogenous syndrome characterized by encephalopathy, focal neurologic findings, and abnormal neuroimaging. Differentiating ADEM from other demyelinating disorders of childhood can be difficult and appropriate interpretation of the historical, clinical, and neurodiagnostic components of a patient's presentation is critical. Myelin oligodendrocyte glycoprotein (MOG) antibody-associated diseases are a recently recognized set of disorders, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(46 citation statements)
references
References 48 publications
4
41
0
Order By: Relevance
“…We observed that sequelae occurred in patients with a more complex clinical onset (visual, motor, behavioural impairment): of those, only few patients received IV immunoglobulins. This is in line with literature [ 69 ].…”
Section: Discussionsupporting
confidence: 94%
“…We observed that sequelae occurred in patients with a more complex clinical onset (visual, motor, behavioural impairment): of those, only few patients received IV immunoglobulins. This is in line with literature [ 69 ].…”
Section: Discussionsupporting
confidence: 94%
“…Typical cerebral MRI lesions were detected in 11 (91.7%) children with MOG-abs and in eight (66.7%) children without MOG-abs, which is similar to what has been reported in previous studies. This finding suggests that children with anti-MOG-ab-associated ADEM have an increased rate of large, bilateral, and widespread lesions, particularly in the cerebral and spinal cord areas ( 6 , 22 ). The most common locations of lesions in both groups were in the supratentorial white matter and thalamus/basal ganglia, which were consistent with the findings of a previous study conducted by Baumann et al ( 23 ).…”
Section: Discussionmentioning
confidence: 94%
“…In most cases, ADEM has a monophasic course and is self-limiting, with return to neurological baseline within 3 months after the onset of symptoms. Occasionally, a subset of ADEM patients with relapsing disorders, including recurrent DEM (RDEM), multiphasic DEM (MDEM), neuromyelitis optica spectrum disorders (NMOSD), and multiple sclerosis have been reported [ 13 ]. The clinical presentation is heterogeneous.…”
Section: Insights In the Acute Disseminated Encephalomyelitis (Adem)mentioning
confidence: 99%